2000
DOI: 10.1016/s0035-9203(00)90424-3
|View full text |Cite
|
Sign up to set email alerts
|

Household risk factors for malaria among children in the Ethiopian highlands

Abstract: Malaria transmission varies from village to village and even from family to family in the same village. The current study was conducted in northern Ethiopia to identify risk factors responsible for such variations in a hypoendemic highland malaria setting: 2114 children aged < 10 years living in 6 villages situated close to small dams at altitudes from 1775 to 2175 m were monitored. Monthly malaria incidence was determined 4 times over a 1-year period during 1997. Incidence results were then analysed by 14 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
187
6
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(212 citation statements)
references
References 23 publications
18
187
6
1
Order By: Relevance
“…The moderate increase in malaria risk associated with poor housing quality and high vegetation coverage in the residential compound observed in this study are consistent with findings in the literature. [27][28][29] However, a risk factor analysis done on a subset of these study data found that housing quality was not significantly associated with in multivariable analysis. 17 It is noteworthy that the area of high malaria transmission adjacent to the major vector breeding site contained predominately poor-quality housing, making it difficult to isolate the effect of housing on malaria risk in the study population.…”
Section: Discussionmentioning
confidence: 70%
“…The moderate increase in malaria risk associated with poor housing quality and high vegetation coverage in the residential compound observed in this study are consistent with findings in the literature. [27][28][29] However, a risk factor analysis done on a subset of these study data found that housing quality was not significantly associated with in multivariable analysis. 17 It is noteworthy that the area of high malaria transmission adjacent to the major vector breeding site contained predominately poor-quality housing, making it difficult to isolate the effect of housing on malaria risk in the study population.…”
Section: Discussionmentioning
confidence: 70%
“…We did observe statistically significant associations between housing conditions and malaria occurrence in this study, with huts having a negative and significant association with malaria incidence (Ghebreyesus et al, 2000;Snow et al, 1998). The material of the roof and ownership of the house are not influential.…”
Section: Malaria I =A 0 +B 1 (Electricity For Lighting) I + B I X I +contrasting
confidence: 40%
“…These apparently large contrasts in host choice by An. gambiae in East and West Africa may result from between-site differences in innate behavioural traits of the vectors (Touré et al, 1994;Lanzaro et al, 1998;COETZEE et al, 2000), spatial relationships of hosts, vectors and larval habitats (Kitron & Spielman, 1989;Kitron, 1998), personal protection (Lindsay et al, 1989 or housing design (Gamage-Mendis et al, 1991;Ghebreyesus et al, 2000). Of these factors, the unusually longstanding and widespread use of bednets in The Gambia deserves particular attention because such domestic personal protection measures can discourage feeding on humans and reduce human blood indices (Garrett-Jones, 1964;Charlwood & Graves, 1987;Lindsay et al, 1989;Githeko et al, 1996a;Bøgh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the proximity of livestock to humans can increase the rate at which zoophilic vectors encounter and feed upon humans (Schultz, 1989;Hewitt et al, 1994). Such effects may explain the direct correlation observed between livestock ownership and malaria burden in some communities Bouma & Rowland, 1995;Mbogo et al, 1999;Ghebreyesus et al, 2000). The impacts of host availability on these other important predictors of EIR, and on its distribution, deserve more detailed study so that, among other things, the impact of livestock management on malaria transmission can be adequately understood and managed (Service, 1991;Mutero et al, 1999).…”
Section: Discussionmentioning
confidence: 99%